Professor Giddings on the Theory of Capital - Boehm-Bawerk, E. v. (Quarterly Journal of Economics, 1890)
Professor Giddings on the Theory of Capital E. v. Boehm-Bawerk E. v. Boehm-Bawerk Vienna, February 3, 1890 Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 4, Issue 3, April 1890, Pages 347–349, https://doi.org/10.1093/qje/4.3.347 Published: 01 April 1890